Cilia and transcription: a mini review - Brown, Jason M. (Frontiers in Cell and Developmental Biology, 2025)
Cilia assembly is accompanied by rapid and highly coordinated transcription of hundreds of genes. Cilia gene regulation has been studied extensively in both metazoans and unicellular model organisms. The forkhead and RFX family transcription factors regulating cilia genes in animals were first identified 25 years ago and considerable molecular details of the regulatory processes have been described since then. While many of the most important early studies of cilia gene regulation were done in unicellular organisms, additional molecular players need to be discovered for a more complete understanding in these organisms. In this concise review, written primarily for students new to the field, I present a brief history of research on cilia gene regulation, highlight some key metazoan discoveries from the last decade, and discuss gaps in our understanding of cilia gene regulation in unicellular model organisms with a focus on Chlamydomonas reinhardtii.